(untitled) (Global Journal of Management and Business Research, 2014)
This study investigate Bond has a debt instruments’ use to finance capital project by different levels of governments. Public utility such as roads, sea and air ports etc in any economy can be attributed or measured to an extent of the amount of money invested on bonds or the amount of Bond issued to finance public utility. However, Empirical evidences attest to the fact that bond is designed to finance capital projects in advance country but in the case a developing economy the reverse is the case hence making it difficult for business organizations to tap unto this financing window. This research work try to capture the effect of bonds on public utility using infrastructural development as a dependent variable in Nigeria with data from 1980 to 2011.